Drought associated miRNAs of Hevea brasiliensis: Identification of markers for drought tolerance - Kuruvilla L; Sathik M B M; Thomas M (PLACROSYM XXII. 22nd Biennial Symposium on Plantation Crops: Leveraging Innovation System in Plantation Sector Through Value Addition, 15-17 December 2016, Indian Council of Agricultural Research-Central Plantation Crops Research Institute, Kasaragod, India. Abstracts. p.204.)
Drought is one of the most significant environmental stress factors that restrict the expansion of rubber cultivation to non-traditional areas where the climatic conditions are characterized by long dry periods, high temperatures and low atmospheric humidity for almost half of the year. The varieties of Hevea like RRII 105 being cultivated in traditional regions do not perform well in such regions. It is essential to identify or develop clones that can withstand such extreme weather factors without compromising on yield and productivity. This study was initiated with an objective to identify and characterise drought responsive miRNAs from Hevea in order to find miRNAs that are associated with drought tolerance which can be used as markers. Next generation sequencing using illumina HiSeq method revealed the expression of 33 conserved miRNA families and 32 novel miRNAs altogether in the drought treated and control samples. Among this, based on differential gene expression analysis, 16 conserved and four novel miRNAs were selected for further quantitative expression analysis using real time PCR. The results showed two novel miRNAs (HbmiRn_63 and HbmiRn_42) as well as miR168 and miR160 to have stronger association with drought tolerance. When expression analysis of three selected miRNAs was studied in known tolerant and susceptible clones as well as germplasm accessions, the results validated their tolerance/susceptibility and confirmed that these miRNAs can be used as markers for drought tolerance in Hevea.
Keywords: Drought; Drought tolerance; Markers; miRNA